The Quality of Sustainability Reporting by Infrastructure Sector Companies Listed on the Indonesia Stock Exchange for the 2020–2024 Period - Muhardi Achmad; Mukhzarudfa Mukhzarudfa; Wiwik Tiswiyanti; Ratih Kusumastuti (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to investigate the quality of sustainability reporting of infrastructure sector companies listed on the Indonesia Stock Exchange for the period 2020-2024. The sample consisted of 6 companies from the infrastructure sector (out of 70 companies) chosen by purposive sampling, based on consistency and availability of sustainability reports during the observation period. The degree of compliance with disclosure requirements was quantified using dichotomous scoring. The findings indicate a steady improvement in the quality of sustainability reporting, with the total ESG compliance score reaching 54.31%. The average compliance score rose from 39.35% in 2020 to 67.44% in 2024. The main results show that environmental disclosure significantly improved after the adoption of GRI Standards 2021, while governance reached the highest level of compliance, indicating a change in corporate transparency and responsibility.